2017
DOI: 10.26740/jdmp.v1n1.p7-14
|View full text |Cite
|
Sign up to set email alerts
|

Gaya Kepemimpinan Kepala Sekolah dalam Upaya Meningkatkan Kinerja Guru dan Tenaga Kependidikan

Abstract: Kepemimpinan dalam pendidikan menjadi kunci dalam pelaksanaan pendidikan yang efektif. pemilihan gaya kepemimpinan yang tepat oleh kepala sekolah akan mampu membawa sekolah kearah peningkatan kualitas dan pelayanan. penelitian ini bertujuan untuk mendeskripsikan dan menganalisis tentang gaya kepemimpinan kepala sekolah dalam upaya meningkatkan kinerja guru dan tenaga kependidikan Di SD Negeri Babatan I/456 Surabaya dan menelusuri tentang faktor yang mempengaruhi gaya kepemimpinan kepala sekolah di SD Negeri Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
16

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 0 publications
0
9
0
16
Order By: Relevance
“…The results of this study also found that the actions of school principals who were relatively well turned out to be not directly in line with school performance achievements. However, a number of studies have shown that the principal's leadership contributes to teacher performance (Apriani, Maria, & Yulianto, 2017;Octavia & Savira, 2016), teacher work productivity (Lestari, Hidayat, & Putra, 2018) and students' outcomes (Pina, Cabral, & Alves, 2015). This finding gives a clue that school performance is not only determined by the principal's leadership variable, but there are a number of other variables.…”
Section: Principal's Leadership Behaviormentioning
confidence: 99%
“…The results of this study also found that the actions of school principals who were relatively well turned out to be not directly in line with school performance achievements. However, a number of studies have shown that the principal's leadership contributes to teacher performance (Apriani, Maria, & Yulianto, 2017;Octavia & Savira, 2016), teacher work productivity (Lestari, Hidayat, & Putra, 2018) and students' outcomes (Pina, Cabral, & Alves, 2015). This finding gives a clue that school performance is not only determined by the principal's leadership variable, but there are a number of other variables.…”
Section: Principal's Leadership Behaviormentioning
confidence: 99%
“…and teacher performance at public secondary schools in Kutai Kartanegara, East Kalimantan Province. The conceptualization of school leadership and supervision used in this study is guided by findings from several studies on principals' leadership and supervision styles (eg, Zuldesiah et al, 2021;Octavia & Savira, 2017). Consistent with this theoretical perspective, our research discusses two questions regarding the leadership style and supervision of principals in improving teacher performance, namely how are efforts to improve teacher performance in public high schools in Kutai Kartanegara Regency in terms of principals' leadership and supervisory styles?, and what are the steps for providing academic supervision that can improve teacher competence in terms of academic potential and the ability to develop learning implementation plans?…”
Section: Introduction *mentioning
confidence: 97%
“…It is a reality in the demands of modern times that the world of education is increasingly complex and requires organization in all fields. To organize well, capable and tough personal are needed (Octavia & Savira, 2017). This person is called the Education Leader (Hashim, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Every leader in carrying out their duties certainly has their own style that we often encounter in everyday people's lives. There are 4 types of leadership according to Octavia & Savira (2017) and Usman (2015), namely: (1) Authoritarian type is this type of leader who wants to be more powerful, the atmosphere at school is always tense, leaders do not give freedom to group members to take part in deciding an issue. (2) Laizze-Faire type, the leadership trait of the Laizzes-Faire type seems invisible because in this type a leader gives full freedom to its members in carrying out their duties.…”
Section: Introductionmentioning
confidence: 99%